The Role of Corporate Social Responsibility (CSR) in Enhancing Brand Image: A Comparative Study in the Indonesian and Kazakhstani Markets - Gerardine Doyle; Claire Gubbins; Siobhan McHale (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Corporate Social Responsibility (CSR) has become an essential strategy for building a positive brand image and fostering customer trust. This study compares the role of CSR in enhancing brand image within Indonesian and Kazakhstani markets, focusing on sectors with high consumer visibility. Through a survey of consumers and interviews with CSR managers, the research identifies key CSR activities that resonate with each market's audience. The study concludes that culturally tailored CSR initiatives can significantly enhance brand perception, suggesting that firms should adapt their CSR strategies to align with local values and consumer expectations.